Psychological capital and the role of perceived organizational support in determining psychological wellbeing among the UK & the India Bank employees - Anand, Shweta (2022)
Background: Over the last couple of decades, psychological wellbeing at work has increasingly received research attention, particularly in light of a rise in the prevalence of mental health issues in work sectors that present with high job demand levels. High levels of stress, anxiety and depression have been documented in the banking workforce too and have been associated with personal and organizational factors that can be detrimental to psychological wellbeing at work in various Western and Eastern countries. Within a positive psychology framework, the construct of Psychological Capital (PsyCap) has become pertinent to the study and reinforcement of mental wellbeing in the workplace in terms of its focus on the development of the four dimensions it comprises of, i.e., hope, optimism, resilience, and self-efficacy. While PsyCap as a personal resource has been found to improve psychological wellbeing at work, Perceived Organizational Support (POS) has also been shown to contribute to wellbeing at work as well as to work satisfaction and performance; however, the relationship among PsyCap, POS and psychological wellbeing in the banking sector in either Western or Eastern countries has been under-researched.